Your Regulatory T Cells Are What You Eat: How Diet and Gut Microbiota Affect Regulatory T Cell Development - Tan, Jian; Taitz, Jemma; Sun, Shir Ming; Langford, Lachlan; Ni, Duan; Macia, Laurence (Frontiers in Nutrition, 2022)
Modern industrial practices have transformed the human diet over the last century, increasing the consumption of processed foods. Dietary imbalance of macro- and micro-nutrients and excessive caloric intake represent significant risk factors for various inflammatory disorders. Increased ingestion of food additives, residual contaminants from agricultural practices, food processing, and packaging can also contribute deleteriously to disease development. One common hallmark of inflammatory disorders, such as autoimmunity and allergies, is the defect in anti-inflammatory regulatory T cell (Treg) development and/or function. Treg represent a highly heterogeneous population of immunosuppressive immune cells contributing to peripheral tolerance. Tregs either develop in the thymus from autoreactive thymocytes, or in the periphery, from naïve CD4+ T cells, in response to environmental antigens and cues. Accumulating evidence demonstrates that various dietary factors can directly regulate Treg development. These dietary factors can also indirectly modulate Treg differentiation by altering the gut microbiota composition and thus the production of bacterial metabolites. This review provides an overview of Treg ontogeny, both thymic and peripherally differentiated, and highlights how diet and gut microbiota can regulate Treg development and function.